2008
DOI: 10.1080/02688690701818901
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and surgical outcomes for medial temporal post-traumatic epilepsy

Abstract: A common post-traumatic location of epileptogenesis is the medial temporal lobe despite evidence of associated diffuse or remote cerebral injury. We undertook a review of post-traumatic medial temporal lobe epilepsy (MTLE) patients as part of an overall post-traumatic epilepsy population to assess the extent of cerebral injury sustained by this subpopulation and to establish whether surgical outcome differed from that of a non-traumatically-induced epilepsy population. A retrospective review of 57 patients ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Many previous studies have found no significant differences in postoperative outcome between traumatic and non-traumatic MTLE patients, despite the high frequency of widespread cerebral hemispheric injury in traumatic MTLE cases [1][2][3][4]. In the present case, findings from preoperative examinations and intraoperative ECoG were consistent with typical MTLE.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Many previous studies have found no significant differences in postoperative outcome between traumatic and non-traumatic MTLE patients, despite the high frequency of widespread cerebral hemispheric injury in traumatic MTLE cases [1][2][3][4]. In the present case, findings from preoperative examinations and intraoperative ECoG were consistent with typical MTLE.…”
Section: Discussionsupporting
confidence: 77%
“…Although dual pathology is common in MTLE, past discussions on dual pathology have emphasized congenital migration disorders or neoplasias and have not focused on traumatic lesion [12]. Previous studies of traumatic MTLE have described the coexistence of neocortical damage and HS [1][2][3][4][5]. Schwartz et al [9] examined 21 traumatic MTLE patients and found that 8 patients had cystic change or encephalomalacia in the ipsilateral neocortex on preoperative MRI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations